COVID-19: an Indian perspective - Kadambi, Prahlad (International Journal Of Community Medicine And Public Health, 2020)
Severe acute respiratory syndrome coronavirus 2 is currently spreading globally rapidly. The World Health Organization (WHO) named the virus as the 2019 novel corona virus (2019-nCoV) on January 7, 2020. On February 11th 2020, the illness associated was named as 2019 coronavirus disease (COVID-19). Subsequently, the WHO declared COVID-19 as a pandemic on 11 March 2020. The first case of COVID-19 was reported in India on 30 January 2020 in Thrissur, Kerala. This was the index case in India who tested positive after coming for a vacation. This individual was a student of the University of Wuhan. Subsequent cases were reported in Kerala. Subsequently, the number of cases in India increased to 519 as on 24th March 2020 with mortality in 7 patients as on 22nd March 2020 and 10 patients on 24th March 2020.